2018
DOI: 10.1160/th17-07-0548
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Count, ADAMTS13 Activity, von Willebrand Factor Level and Survival in Patients with Colorectal Cancer: 5-Year Follow-up Study

Abstract: Distant metastasis is a major cause of colorectal cancer-related death, but the mechanism of tumour progression is not fully understood. There is growing evidence of an interaction between tumour cells and platelets which may influence tumour progression and metastasis formation. Quality and quantity of von Willebrand factor may regulate the interaction between tumour cells and platelets. Our aim was to measure the platelet count, von Willebrand factor antigen (VWF:Ag) levels and ADAMTS13 activity in a large (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…line with this, a recent observational study in colorectal patients found that the lower levels of VWF were associated with improved event-free survival and less thrombotic complications. 41 Notably, the plasma concentration of VWF is increased among patients with malignant breast disease. 42 In accordance with our findings, a large British prospective study of cardiovascular disease in 3,810 elderly men found that physical activity was significantly and inversely related with VWF in a dose-response manner.…”
Section: Discussionmentioning
confidence: 99%
“…line with this, a recent observational study in colorectal patients found that the lower levels of VWF were associated with improved event-free survival and less thrombotic complications. 41 Notably, the plasma concentration of VWF is increased among patients with malignant breast disease. 42 In accordance with our findings, a large British prospective study of cardiovascular disease in 3,810 elderly men found that physical activity was significantly and inversely related with VWF in a dose-response manner.…”
Section: Discussionmentioning
confidence: 99%
“…Garam et al found that ADAMTS13 is a prognostic risk factor for colon and liver cancer [ 51 ]. The single nucleotide polymorphism of ADAMTS14 is closely related to liver cancer and oral cancer [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Research on inflammation and inflammatory mediators has revealed that inflammation markers can trigger a premetastatic niche to escape the immunological surveillance and to play decisive roles at every step of tumorigenesis and development. 8 These inflammatory molecules-such as neutrophils, 9 platelets, 10 lymphocytes, 11 fibrinogen (Fib), 12 albumin (Alb), 13 and combinations of several single markers in the forms of ratios, 14,15 which are usually derived from circulating immune cells and acute-phase reactive proteins-have been reported as valuable predictors in a variety of human tumors. Currently, many studies have applied these routine parameters for the diagnosis and prognosis of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%